2018
DOI: 10.1111/echo.14161
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography during preload stress for evaluation of right ventricular contractile reserve and exercise capacity in pulmonary hypertension

Abstract: Objectives Pulmonary hypertension (PH) is characterized by marked and sustained elevation of pulmonary vascular resistance and pulmonary artery pressure, and subsequent right‐sided heart failure. Right ventricular (RV) function and exercise capacity have been recognized as important prognostic factors for PH. Our aim was to investigate RV contractile reserve and exercise capacity during a leg‐positive pressure (LPP) maneuver. Methods The study population comprised 43 PH patients and 17 normal controls. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…However, the strain analysis was not performed in the RV apical view but by with analysis of the six segments in a classical four-chamber view. Sano et al [ 16 ] evaluated the RV contractile reserve using a preload stress echocardiography in patients with pulmonary hypertension compared to healthy volunteers. They reported that RV free wall strain (assess in the RV-focused apical four-chamber view) increased significantly (+3.5%) as well as SV (+8.4 mL) in the healthy volunteer’s group (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, the strain analysis was not performed in the RV apical view but by with analysis of the six segments in a classical four-chamber view. Sano et al [ 16 ] evaluated the RV contractile reserve using a preload stress echocardiography in patients with pulmonary hypertension compared to healthy volunteers. They reported that RV free wall strain (assess in the RV-focused apical four-chamber view) increased significantly (+3.5%) as well as SV (+8.4 mL) in the healthy volunteer’s group (15).…”
Section: Discussionmentioning
confidence: 99%
“…RV free wall longitudinal strain, which is an indicator of RV function at rest, is calculated as the mean of the RV lateral basal, mid, and apical segments, with exclusion of the septal segments. In one study, RV contractile reserve was assessed as the difference in RV free wall strain at rest and during a leg-positive pressure stress [24]. In this study of 43 pulmonary hypertension patients, RV contractile reserve was significantly lower in patients with changes in left ventricular stroke volume < 3.3 mL.…”
Section: Definitions Of Right Ventricular Reservementioning
confidence: 88%
“…We suggest that the E/SV ratio may demonstrate value to identify patients with elevated PCWP under PLL. Earlier studies show a lack of increase in SV during PLL both in patients with PH 14 and in HFpEF. 15 We demonstrate similar findings, suggesting that the inability to augment SV may be owing to the LV operating on the plateau limb of the Frank-Starling curve.…”
Section: Estimation Of Left Ventricular Filling Pressures At Rest Usi...mentioning
confidence: 89%